The Iliad - Homer; Butler, Samuel (Calcutta, India : Projapoti, 2000)
"The Iliad is regarded as the earliest Greek literature. It is the epic story of the climax of the Trojan war. The Greek hero and the warrior Achilles leaves the battlefield to sulk his tent, after his commander-in-chief, Agamemnon confiscates the lovely maid, Briseis. But Achilles is persuaded to rejoin Greek army to face the mighty Trojan hero Hector, following the death of his friend Patroclus. Patroclus was killed by Hector in the battlefield. The Iliad story of heroism and compassion and a reminder of Mycenaean age."--Cover.
Keywords: Achilles -- (Mythological character); Epic poetry, Greek -- Translations into English; Trojan War